MODEL MENTAL MAHASIWA BARU DALAM MEMAHAMI KONSEP STRUKTUR ATOM DITINJAU DARI PENGETAHUAN AWAL - Sunyono Sunyono; Leny Yuanita; Muslimin Ibrahim (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
Several studies have shown that mental models can affect a student's ability to perform reasoning on external representation faced. Student mental models are generally used to thinking in order to solve the problem. This study aims to look at the characteristics of mental models beginning of students in understand the concept of atomic structure. Samples were taken at random from the students of Department of Mathematics and Natural Sciences, class of 2012 with the grouping based on students' prior knowledge. The number of samples involved as many as 72 people consisting of students with the prior knowledge of high, medium, and low. Diagnostic tests are used to see the essays shaped the emergence of mental models.  The results showed that for all groups of prior knowledge, mental models beginning of students in understand the concept of atomic structure is still dominated by verbal mental model with the category of "very bad" and "bad" or the characteristics of mental model "formless/not clear" and mental model "intermediates_1." These results imply that the mental models of students can be used as a reference in setting learning to help students in solving problems related to the three levels of chemical phenomenon. To build a mental models of students towards a better, should be designed study involving interconnected between the third-levels of chemical phenomenon (macro, sub-micro, and symbolic).